Clothing care 2.0: smart hanging clothes rack - Azizul Ahmad, Atiqah Firhanah; Ahmad Affendy, Nuraisyah Ashidqii Afflin; Shaharul Anuar, Nur Hazwani; Mohd Rous, Muhammad Aliff (2024)
An automatic hanging clothes rack is a convenient solution for drying clothes indoors. It typically features a motorised system that raises and lowers the rack, making it easier to hang and retrieve clothes without the need for manual effort. It is especially useful in spaces where traditional drying methods are not feasible, like apartments or homes without outdoor drying space. Some additional details of this rack include adjustable height settings, timers for drying cycles, and built-in sensors to prevent overheating or overloading. Since this rack can be raised and lowered, it is great for saving space in small rooms or apartments. When not in use, it can be raised to the ceiling or a high position, freeing up floor space. It is also convenient because users can simply hang their clothes on the rack, press a button, and let the motorised system take care of the rest. This eliminates the need for manual labour and makes the drying process more efficient. Next, many models are designed to be energy-efficient, using minimal power during operation. This can help reduce electricity bills compared to traditional dryers. While the initial cost of an automatic hanging clothes rack may be higher than a traditional drying rack, it can be a worthwhile investment for those who need a convenient indoor drying solution. Overall, automatic hanging clothes racks offer a convenient, space-saving, and efficient way to dry clothes indoors, making them popular among urban dwellers and those with limited outdoor space.